Review: Marianne Tansman’s "La guitare dans la vie d’Alexandre Tansman" (2018) - Brandão, Luigi; Holler, Marcos (Revista Vórtex, 2019)
This is a review of Marianne Tansman’s book La guitare dans la vie d’Alexandre Tansman, written in 2018. The book consists of a chronological account of the composer’s relation with the guitar and with the guitarist Andrés Segovia, and produces remarks both on the style and particularities of Tansman’s works for guitar as well as broader considerations on Tansman’s artistic point of view. By the end of the text, it is compared to other works on the issue of the guitar in the life of Tansman, and some directions for further research on the subject are suggested.